IMPLEMENTASI TASAWUF DALAM PENDIDIKAN AGAMA ISLAM: INDEPENDENSI, DIALOG DAN INTEGRASI - Benny Prasetiya; Bahar Agus Setiawan; Sofyan Rofi (POTENSIA: Jurnal Kependidikan Islam, 2019)
This paper aims to put forward the implementation of sufism (tasawuf) in the learning of Islamic education which is analyzed by the approach of independence, dialogue, and integration. This discussion finds that Islamic education in the era of globalization is momentum in developing and building competitive Islamic education. Islamic education must be able to face all forms of globalization challenges with their various impacts. The presence of Sufism is the antidote to the problem of the Islamic education being faced. The formation of our human beings from the process of Islamic education made Sufism a method and learning strategy.